2017
DOI: 10.1111/and.12876
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypobaric hypoxia diminishes the expression of base excision repair OGG1 enzymes in spermatozoa

Abstract: Hypobaric hypoxia induces DNA damage in rat testicular cells, the production of defective spermatozoids and decreased sperm count, associated with an increase in oxidative stress. 8-Oxoguanine glycosylase (OGG1) enzymes are main members of the base excision repair (BER) system, a DNA repair mechanism. We determined the expression levels of mitochondrial and nuclear OGG1 isoforms in spermatozoa collected from cauda epididymis in rats exposed to chronic hypobaric hypoxia (CHH) for 5, 15 and 30 days. CHH attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Spermatozoa are cells that are particularly susceptible to oxidative stress given their limited content of antioxidants, and hypoxia exposure has been shown to produce DNA damage in sperm cells [10]. Chronic hypobaric hypoxia (CHH) attenuates 8-oxoguanine glycosylase (OGG1) and OGG1-2a in rat spermatozoa, which may contribute to DNA damage under hypoxia exposure [11]. Hypobaric hypoxia reduces the quality of sperm DNA, including fragmentation and unpacking, and its DNA stability is diminished in the mouse [12].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa are cells that are particularly susceptible to oxidative stress given their limited content of antioxidants, and hypoxia exposure has been shown to produce DNA damage in sperm cells [10]. Chronic hypobaric hypoxia (CHH) attenuates 8-oxoguanine glycosylase (OGG1) and OGG1-2a in rat spermatozoa, which may contribute to DNA damage under hypoxia exposure [11]. Hypobaric hypoxia reduces the quality of sperm DNA, including fragmentation and unpacking, and its DNA stability is diminished in the mouse [12].…”
Section: Discussionmentioning
confidence: 99%
“…; Farias et al . ). Another technique in which progress has been made in detecting damage in specific genes or regions of the genome is reverse transcription polymerase chain reaction (RT‐PCR) (Cawthon ; Bennetts & Aitken ; Fernandez‐Gonzalez et al .…”
Section: Effects Of Cryopreservation On Dna Quality and Gene Expressionmentioning
confidence: 97%
“…Currently, damage to spermatic DNA derived from the effects of ROS is evaluated through classic techniques such as 8-oxodG and 8-oxodA detection. It can be quantified by flow cytometry with specific probes or with a Western blot of 8-Oxoguanine glycosylase (OGG1), allowing the repair expression of OGG1 enzymes in the spermatozoa to be identified and evaluated (Mart ınez-P aramo et al 2009;Shaliutina et al 2013;Farias et al 2018). Another technique in which progress has been made in detecting damage in specific genes or regions of the genome is reverse transcription polymerase chain reaction (RT-PCR) (Cawthon 2002;Bennetts & Aitken 2005;Fernandez-Gonzalez et al 2008;P erez-Cerezales et al 2009).…”
Section: Effects Of Cryopreservation On Dna Quality and Gene Expressionmentioning
confidence: 99%
“…Looking at single base substitution (SBS) signatures, more hypoxic tumors experienced signatures with etiology of defective homologous recombination-based repair and DNA mismatch repair (MMR) ( Bhandari et al, 2020 ). In vitro investigations have shown that hypoxia could lead to genomic instability through its downregulation of DNA repair genes and their respective pathways of MMR ( Lu et al, 2014 ; Cowman et al, 2021 ), homologous recombination repair (HRR) ( Bindra et al, 2005 ; Fanale et al, 2013 ), base excision repair (BER) ( Chan et al, 2014 ; Farias et al, 2018 ) and Fanconi anemia ( Scanlon and Glazer, 2014 ) (reviewed in ( Luoto et al, 2013 ; Begg and Tavassoli, 2020 )). Hypoxia has additionally been implicated in the repression of DNA replication genes and increased replication stress through stalled replication forks and decreased new origin firing that is time and oxygen dependent ( Pires et al, 2010 ; Ng et al, 2018 ) (reviewed in ( Luoto et al, 2013 ; Begg and Tavassoli, 2020 )).…”
Section: Introductionmentioning
confidence: 99%